Contract manufacturing service quality and its relationship with customer satisfaction and loyalty in F&B industry / Zulkefli Abdul Rahim - Abdul Rahim, Zulkefli (Institute of Graduate Studies, UiTM, 2018)
Business environment is highly competitive especially for the low entry barrier industry such as F&B industry, characterized by low high-tech involvement. As a result, the industry draws high number of players competing for the target markets. In order to sustain the business as well as to improve their financial performance, F&B manufacturers opt to offer contract manufacturing services (CMS) while marketing intermediaries contracted-out their products. There is a formal relationship established between the service provider and the buyer. However, the impact of service quality on retaining the business relationship particularly has not been empirically investigated. To fill this gap, this study explores the determinants of contract manufacturing service quality (CMSQ) and the interrelationship among CMSQ, customer satisfaction and loyalty of the F&B CMSs' customers in Malaysia. Four focus group interviews (28 participants) were held in this study using a semistructured guide questions and they comprised 12 contract manufacturers and 16 business customers. The participants were the key personnel, representing organizations that are actively engaged in CMS. Three new dimensions were discovered from the focus group interviews; product development capability, Halal and outcome quality in addition to the SERVQUAL dimensions…